THE GREEN ALCHEMY: INNOVATION IN PROCESSING COCOCNUT PULP INTO SUPERFOOD FLOURS - Ernida Mahmud; Zulkifli Ayub; Widya Wahyuni Asnur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to empower the community in Jeppe'e Village, West Tanete Riattang District, Bone Regency through innovation in the use of coconut pulp waste into superfood flour products with high economic value. The background of this research problem is the lack of optimal utilization of abundant coconut pulp waste in the region and limited public access to value-added processing technology. The method of implementing this research uses a participatory empowerment approach combined with the Production Training and Assistance model with the planning, acting, observing, and reflecting stages. The participants of this study were 40 people who were selected by purposive sampling. The results of the study showed that the empowerment program succeeded in increasing the knowledge and technical skills of the community in processing coconut pulp into superfood flour, there was a significant change in the behavior of participants from initially skeptical to motivated to develop their business independently, and the formation of awareness of the economic potential of agroindustrial waste. The conclusion of this study is that the empowerment program has succeeded in increasing the technical capacity of the community, opening up opportunities for the development of community-based productive business units, and contributing to the reduction of coconut pulp waste that is discarded into the environment.